Laboratory Experiments on the Influence of the Wave Spectrum Enhancement Factor on a Rubble Mound Breakwater - Hosny Bakali; Ismail Aouiche; Najat Serhir; Youssef Zahir; El hassan Ziane; Abderrazak Harti; Zakariae Zerhouni; Edward Anthony (Journal of Marine Science and Engineering, 2022)
This paper experimentally explored the influence of the wave spectrum shape variation on breakwater design. The energy spectrum function generally considered for the design of coastal structures is the JONSWAP spectrum. The laboratory results were therefore used to assess the impact of changing the spectrum shape parameter (PEF). We analysed armour stability and wave overtopping in a wave flume with a geometric similarity ratio of 1:30. The experimental results showed that the PEF has maximum influence on overtopping and wave pressures on the crown wall. For a PEF value of 3.3, overtopping was much higher (30% to 100% higher) than with a PEF of 1. Pressure on the crown wall was 20% higher with a PEF of 3.3 in comparison with that for a PEF equal to 1. The stability of the breakwater’s block armour is less sensitive to the PEF variation.